2003
DOI: 10.2105/ajph.93.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination and Depression: Moderating Effects of Coping, Acculturation, and Ethnic Support

Abstract: The authors evaluated the effects of cultural norms and social contexts on coping processes involved in dealing with perceived racial discrimination. Cross-sectional data derived from personal interviews with Korean immigrants residing in Toronto were analyzed. Among the respondents, active, problem-focused coping styles were more effective in reducing the impacts on depression of perceived discrimination, while frequent use of passive, emotion-focused coping had debilitating mental health effects. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
609
3
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 710 publications
(667 citation statements)
references
References 25 publications
47
609
3
8
Order By: Relevance
“…Depression was chosen as an indicator of psychological distress because it is one of the most prevalent mental health problems in the United States (Kessler, 1997(Kessler, , 2002 and because of its well-established association with perceived racism and discrimination (Landrine & Klonoff, 1996;Noh & Kaspar, 2003). Depressive symptoms were measured using the Center for Epidemiological Studies Depression Scale (CES-D; Radloff, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…Depression was chosen as an indicator of psychological distress because it is one of the most prevalent mental health problems in the United States (Kessler, 1997(Kessler, , 2002 and because of its well-established association with perceived racism and discrimination (Landrine & Klonoff, 1996;Noh & Kaspar, 2003). Depressive symptoms were measured using the Center for Epidemiological Studies Depression Scale (CES-D; Radloff, 1977).…”
Section: Methodsmentioning
confidence: 99%
“…These protective effects are further documented in intervention studies with non-immigrants (Dobkin et al, 2002;Thompson et al, 2001), and while similar results can be observed with immigrant populations (Agudelo-Suarez et al, 2009;Noh & Kaspar, 2003), the effect is much more variable (Tsai & Thompson, 2013).…”
Section: Coping Resources and Mental Health Problemsmentioning
confidence: 66%
“…For example, it has been shown that gender and racial discrimination is associated with hypertension (e.g., Krieger, 1990), perceived discrimination with depression (e.g., Noh & Kaspar, 2003), and that there is association between stressful environment and changes to corticoids levels (e.g., Pennington, 2002), and yet Szasz invalidates experiences of the oppressed and existence of mental illness. He does so from the point of privilege: able-bodied, White male, of upper-middle socioeconomic status (SES) and of aristocratic background.…”
Section: Example Of This In the Myth Of Mental Illness: Foundations Omentioning
confidence: 99%